Analysis of Strategies in Increasing Competitiveness at E11evenkick Academy in Makassar City - Muhammad Rifqi Azhar; Anwar; Muh. Ichwan Musa; Siti Hasbiah; Muhammad Ilham Wardhana Haeruddin (PT. Maju Malaqbi Makkarana, 2023)
Strategy Analysis in Increasing Competitiveness at E11evenkick Academy in Makassar City. Thesis Faculty of Economics and Business, Makassar State University Supervised by Anwar and Muh. Ichwan Musa. This study aims to determine strategies for increasing competitiveness at E11evenkick Academy in Makassar City. The type of research used is descriptive qualitative. Descriptive, namely research that aims to describe the nature, circumstances, phenomena, of an individual or group that you want to study. Qualitative research emphasizes quality not quantity and the data collected does not come from questionnaires but comes from interviews, direct observation and other related documents, and in this study the respondents are known as resource persons. The findings of this study explain that E11evenkick Academy is being faced with threats from outside the company but currently these threats can be suppressed and minimized by maximizing and optimizing the internal strengths of E11evenkick Academy. Based on the SWOT analysis, E11 Evenkick Academy is in quadrant II of the SWOT diagram. The strategy that must be implemented is to use the company's strengths to take advantage of long-term opportunities by way of a diversification strategy. The diversification strategy in question is how E11evenkick Academy can increase growth, sales and profits through expanding its market sector. This strategy will serve as the basis for E11evenkick Academy to increase competitiveness, especially in Makassar City.